Effects of dietary chitosan diets on growth performance in broiler chickens - Oraya Khambualai (2018)
The objective of the present study was to investigate the effects of a low percentage of dietary chitosan on growth performance, carcass quality, plasma cholesterol, triacylglycerol levels, and the concentration of plasma very low density lipoprotein (VLDL) levels in broilers. Three hundred and sixty male Arbor Acre broiler chicks were randomly allotted into 4 groups with 3 replicates of 30 chickens per replicate. Chitosan was supplemented to a basal diet at 0 (control), 0.01, 0.03 and 0.06% for 7 weeks. Basal diet was starter (21% CP, 3200 kcal/kg ME) at 0-3 weeks, grower (19% CP, 3200 kcal/kg ME) at 3-6 weeks and then changed to finisher (17% CP, 3200 kcal/kg ME) until 7 weeks. Compared with the control, body weight, feed efficiency, and weights of drumstick and breast tended to increase in all chitosan groups, although not statistically significant. The weight of visceral organs and the total plasma cholesterol, triacylglycerol and VLDL levels did not show a significant difference among the groups. These results suggest a low level of dietary chitosan tended to improve growth performance. These results suggest that a low level of dietary chitosan diet for broilers cannot reduce the total plasma cholesterol, but tended to have better growth performance. Copyright © 2008, Japan Poultry Science Association.